PENGARUH KINERJA PEGAWAI TERHADAP KUALITAS PELAYANAN APLIKASI MOBILE JAMINAN KESEHATAN NASIONAL (JKN) KEPADA PESERTA BPJS KESEHATAN CABANG DENPASAR - Ni Putu Eka Purnamayanti; I Dewa Ayu Putri Wirantari; Juwita Pratiwi Lukman (Cahaya Ilmu Bangsa, 2025)
This study aims to determine the effect of employee performance on the service quality of the Mobile Jaminan Kesehatan Nasional (JKN) application for BPJS Kesehatan participants at the Denpasar Branch. This research is a quantitative study with an associative causal approach, aiming to explain the influence relationship between independent and dependent variables through hypothesis testing. The study uses a sample of 100 respondents, with questionnaires distributed online via Google Forms. The sampling technique applied is non-probability sampling using purposive sampling. The sample consists of users of the Mobile JKN application in Denpasar City. The research instruments include validity testing, reliability testing, classical assumption tests, and simple linear regression analysis using SPSS version 26. Hypothesis testing is conducted using the t-test, and the results indicate that employee performance has a positive and significant effect on the service quality of the Mobile JKN application.